The Growth and Longevity of Chamelea gallina (Mollusca, Veneridae) in the Black Sea - Boltacheva, N.A.; Mazlumyan, S.A. (Інститут зоології ім. І. І. Шмальгаузена НАН України, 2003)
При исследовании радиальных срезов раковин Chamelea gallina (Linnaeus, 1758) выявлены годичные слои роста, что позволило определить возраст моллюсков и продолжительность их жизни. Максимальный возраст моллюсков, определенный по эталонным экземплярам — 9 лет. Полученные данные сопоставлены с известными для популяции этого вида из Средиземного моря. Показано, что при значительно различающихся темпах роста моллюсков из разных частей ареала, предельные размеры раковины близки. Annual growth rings were found in the study of shell sections of Chamelea gallina (Linnaeus, 1758), from which the age and the longevity of Chamelea gallina were determined. Based on standard individuals, maximum age of molluscs was assessed as 9 years. Results obtained are compared with those known for Mediterranean population of the same species. It was also found that Chamelea gallina collected from different localities of the same area have comparable maximum shell length but considerably differ in the growth rate.